Oxidation Study of Oleocanthal and Oleacein Induced by Oxone - Antoniadi, Lemonia; Angelis, Apostolis; Kostakis, Ioannis K.; Skaltsounis, Leandros A. (Planta Medica, 2024)
A selective Oxone-induced oxidation of oleocanthal and oleacein, the two main secoiridoids of olive oil, to their bis-oxidized products is described. This protocol is based on a Baeyer-Villiger mechanism and the concentration of Oxone in the final solution. The bis-oxidation of the aldehydic compounds could be extended for the synthesis of various semisynthetic analogs. The obtained acids exhibit strong antioxidant activity, being efficient free radical scavengers.
Keywords: Oleocanthal; oleacein; oleocanthanonic acid; oleaceinonic acid; Olea europaea; Oleaceae; Baeyer-Villiger oxidation; antioxidant activity